Analisis Kualitas Pembangunan Jaringam Fiber To The Home Iconnet Pada Area Cluster Padang Barat - Ahmad Zaki; Ahmaddul Hadi; Syukhri Syukhri; Hadi Kurnia Saputra (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
Fiber To The Home (FTTH) networks have become an important communications infrastructure that meets the need for fast and reliable internet connectivity in various communities. The aim of this research is to provide a comprehensive analysis of FTTH network development, focusing on the factors that influence the quality of FTTH networks and their impact on society and industry. The research method used, among others, is quantitative by measuring the IN and OUT attenuation parameters at the Optical Distribution Point using an Optical Power Meter measuring instrument. Then the results are compared with the TIPHON/ITU-T Packet Loss standard. The analysis results show that IN and OUT attenuation greatly influences the quality of the FTTH network. The results of the total attenuation analysis on Line A show that the attenuation that has been compared using Packet Loss has a total attenuation difference of 1.11% to 1.37%, on Line B 1.07% to 1.49%, on Line C 1.27% to 1.43%, and on Line D 1.16% to 1.56% the difference obtained during the research can still be said to be quite feasible and good for use by customers. By considering these factors, it is hoped that the construction of an FTTH network can provide maximum benefits for society and industry in supporting economic growth and technological progress.